Pergulatan Politik Pesantren Era Reformasi: (STUDI INTERAKSI PESANTREN DENGAN PARTAI POLITIK DI KAB. BANYUMAS) - Nugroho, Anjar (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
The focus of this study examines the role of pesantren politics during the reform period; the form of political maneuvering of political parties as well as the current pesantren response, as well as the background of thought and reasons raised by pesantren. Particularly to be analyzed is the relation of pesantren with economic and political interests in the multi-party reform era political configuration.For the pesantren leader (kiai) in Banyumas, politics really is a necessity that can be done by all components of the nation, which can be done in various ways. Although most of the pesantren leaders (kiai) in Banyumas show an open attitude towards political parties, especially political parties based on Islam, but in their concrete choices are influenced by various factors, especially cultural (ideological) and structural (organizational) factors. Second, for political parties, the kiai's position is crucial to provide political and cultural legitimacy to his constituents.